PENGARUH KEPEMIMPINAN KEPALA DESA, KOMPETENSI APARAT DESA DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN DANA DESA DI DESA HILINA’A KECAMATAN GUNUNGSITOLI - Fatolosa Hulu; Rida Rahim (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study examines the influence of village head leadership, village apparatus competence and community participation on village fund management in Hilina'a Village, Gunungsitoli District, Gunungsitoli City. To answer the research objectives, three hypotheses were formulated, namely leadership, competence and community participation in managing village funds. The research approach used is quantitative. Data was collected using a questionnaire, of the 61 questionnaires distributed to the apparatus and the Hilina'a village community, 57 questionnaires were returned. Hypothesis testing, used regression analysis using SPSS version 22.00. Before testing the hypothesis, the validity, reliability and classical assumptions were tested first. The results of this study indicate that leadership, competence and community participation have a positive and significant effect on the management of village funds